List-colourings of near-outerplanar graphs - Hetherington, Timothy J. (2007)
A list-colouring of a graph is an assignment of a colour to each vertex v from its own list L(v) of colours. Instead of colouring vertices we may want to colour other elements of a graph such as edges, faces, or any combination of vertices, edges and faces. In this thesis we will study several of these different types of list-colouring, each for the class of a near-outerplanar graphs. Since a graph is outerplanar if it is both K4-minor-free and K2,3-minor-free, then by a near-outerplanar graph we mean a graph that is either K4-minor-free or K2,3-minor-free.